Fizikalno ozadje delovanja hidravličnih sistemov - Lovrec, Darko (University of Maribor Press, 2018)
Physical Background of Hydraulic Systems. Hydraulic drive technology is indispensable in areas where it is crucial to move large loads with high dynamics. This includes all major transforming and processing machines, agricultural, forestry and construction machinery, aviation and nautics. For all these machinery the transmission of forces and movements is based on the use of a hydraulic fluid. The textbook Physical background of hydraulic systems gives a more detailed insight into the hydraulic transmission of power, forces and motions, and signals through hydraulic fluid. It is intended for students of university study program in mechanical engineering and anyone interested in hydraulic power transmission, with all its details and special features. The basis comes from fluid mechanics and known physical bases, which, with simplifications and assumptions, lead to useful equations typical for the field of hydraulic drive and control techniques. The textbook is the first in a series of textbooks, which, as stand-alone books, deal with all segments of hydraulic drive technology from hydraulic pumps and control valves to other hydraulic equipment. Knowing the physical functioning of hydraulic systems is not only necessary for the basic calculations and selection of suitable hydraulic components. It is also indispensable for maintaining these systems and for identifying anomalies in the operation of these systems - for distinguishing between the mode of operation typical for hydraulic drives, and the unusual operation resulting from a fault or change.